2019
DOI: 10.1073/pnas.1818544116
|View full text |Cite
|
Sign up to set email alerts
|

PGE 2 signaling via the neuronal EP2 receptor increases injury in a model of cerebral ischemia

Abstract: The inflammatory prostaglandin E2 (PGE 2 ) EP2 receptor is a master suppressor of beneficial microglial function, and myeloid EP2 signaling ablation reduces pathology in models of inflammatory neurodegeneration. Here, we investigated the role of PGE 2 EP2 signaling in a model of stroke in which the initial cerebral ischemic event is followed by an extended poststroke inflammatory response. Myeloid lineage cell-specific EP2 knockdown in Cd11bCre;EP2 lox/lox mice attenuated brain infiltration of Cd11b + CD45 hi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 49 publications
1
63
0
Order By: Relevance
“…More importantly, our finding raises the possibility that an EP2 antagonist could be used as a potential therapy to oppose neuroinflammation in RP. Consistent with our findings, EP2 deletion is reported to reduce inflammation and pathology in other neurodegenerative disorders [10][11][12]31]. The previous data together with our current findings suggest a general and critical role for EP2 receptor in neuroinflammation and neurodegeneration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More importantly, our finding raises the possibility that an EP2 antagonist could be used as a potential therapy to oppose neuroinflammation in RP. Consistent with our findings, EP2 deletion is reported to reduce inflammation and pathology in other neurodegenerative disorders [10][11][12]31]. The previous data together with our current findings suggest a general and critical role for EP2 receptor in neuroinflammation and neurodegeneration.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicated that COX-1 deletion abrogated PGE2 elevation in the rd10 retina, suggesting that COX-1 primarily droved the observed increase in PGE2 in the rd10 retina. The receptor EP2, one of PGE2 downstream G-protein coupled receptors, is highly expressed in microglia in the brain [10][11][12]. To examine whether downregulation of PGE2 affected EP2 expression in the microglia of the COX-1 −/− / rd10 retina, we performed qPCR in sorted primary microglial cells by using flow cytometry.…”
Section: Cox-1 Deletion Reduces Microglia Activation and Alleviates Nmentioning
confidence: 99%
“…Moreover, for ischemic stroke patients, the effective therapeutic time window is approximately 4 hr (Shen et al, ). The inflammatory response lasts a long time after stroke onset, and anti‐inflammation therapy has been considered as a promising strategy in extending the therapeutic time window (Lambertsen et al, ; Liu et al, ; Shichita et al, ). The use of kellerin, a natural neuroinflammatory inhibitor, in overcoming the time window limitation in stroke therapy will potentially be of great clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pharmacological activation of EP2 by ONO-AE1-259-01 significantly reduced the infarct volume in mice (Ahmad et al, 2010). However, recent studies demonstrated that neuronal EP2-receptor expression is induced after cerebral ischemia (Liu et al, 2019). Validation of the anti-EP2 antibody used in that study was performed by using cerebellar lysates and HEK cells overexpressing the EP2 receptor.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Validation of the anti-EP2 antibody used in that study was performed by using cerebellar lysates and HEK cells overexpressing the EP2 receptor. The blockade of EP2 in mice contributed to cerebro-protection by reducing neuroinflammation (Liu et al, 2019), and EP2 knockout mice were shown to be more protected from intracerebral hemorrhage strokes (Leclerc et al, 2015b).…”
Section: Cardiovascular Systemmentioning
confidence: 99%